(untitled) (KYAMC Journal, 2021)
Background: The rupture of fetal membrane before onset of labour at less than 37 completed weeks of gestation. Incidence of Preterm prelabour rupture of membrane (PPROM) ranges from 3.0-10.0% of all deliveries and causes around 25-30% of all preterm deliveries. Objective: To see the clinical profile, maternal and fetal outcome of preterm prelabour rupture of the membrane. Materials and Methods: One hundred fifteen pregnant women with 28-37 weeks of gestation and diagnosed as PPROM admitted in different units selected by purposive sampling, fulfilled the inclusion and exclusion criteria were enrolled as study population in this study. Results: The mean age was 24.65(±3.68) years. Majority (75.65%) were primi para. The mean gestational age was 32.34(±2.86) weeks, 79.13% had gestational age between 30-36 weeks and 20.87% had up to 30 wks. The common risk factors of the study population were history of coitus, CPD, infection and history of abortion which were 42.61%, 9.57%, 5.22% and 4.35% respectively. Majority 55.65% women had vaginal delivery, 44.35% had caesarian section. Majority of the babies born to PPROM group were in the very low birth weight category (53 cases 62.3%), whereas only 32 cases (37.6%) were of normal birth weight. Infection and perinatal mortality was significantly associated with PPROM. Conclusion: PPROM can be prevented avoiding the certain risk factors by proper ante natal checkup, strict follow up, good obstetrical care and perinatal care , making mass awareness of the sequele. KYAMC Journal. 2021;12(3): 166-171